Odpowiedzi

2010-03-28T21:33:04+02:00
A)(4-2X)-(X+3)=(X-5)-(-3-X)
4-2x-x-3=x-5+3+x
-2x-x-x-x=-5+3+3-4
-5x=-3|:-5
x=3/5

b)(3-2x)+(3x+4)=-(3-2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
-2x+3x-2x-5x=-3+4-3-4
-6x=-6|-6
x=1

c)-(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
-x+2x-4x-x=1+3+3+1
-4x=8|:-4
x=-2

d)-(X+3)-(2X+8)=(-3-2X)+(2X+1)
-x-3-2x-8=-3-2x+2x+1
-x-2x+2x-2x=-3+1+3+8
-3x=9|:-3
x=-3
2 5 2
2010-03-28T21:40:16+02:00
A) (4-2x)-(x+3) = (x-5)-(-3-x)
4-2x-x-3 = x-5+3+x
1-3x = 2x-2 /+2
3-3x = 2x /+3x
3 = 5x /:5
x = 0,6

spr: (4-2×0,6)-(0,6+3) = (0,6-5)-(-3-0,6)
(4-1,2)-3,6 = -4,4-(-3,6)
2,8-3,6 = -4,4+3,6
-0,8 = -0,8
L=P

b) (3-2x)+(3x+4) = -(3-2x)+(5x+4)
3-2x+3x+4 = -3+2x+5x+4
7+x = 1+7x /-x
7 = 1+6x /-1
6 = 6x /:6
x = 1

spr.: (3-2×1)+(3×1+4) = -(3-2×1)+(5×1+4)
(3-2)+(3+4) = -(3-2)+(5+4)
1+7 = -1+9
8 = 8
L = P

c) -(x+3)+(2x-1) = (1+4x)+(3+x)
-x-3+2x-1 = 1+4x+3+x
x-4 = 4+5x /-x
-4 = 4+4x /-4
-8 = 4x /:4
x = -2

spr.: -(-2+3)+(2×(-2)-1) = (1+4×(-2))+(3+(-2))
-1+(-4-1) = (1+(-8))+1
-1+(-5) = -7+1
-6 = -6
L = P

d) -(x+3)-(2x+8) = (-3-2x)+(2x+1)
-x-3-2x-8 = -3-2x+2x+1
-3x-11 = -2 /+11
-3x = 9 /:(-3)
x = -3

spr.: -(-3+3)-(2×(-3)+8) = (-3-2×(-3))+(2×(-3)+1)
-(-6+8) = (-3-(-6))+(-6+1)
6-8 = (-3+6)+(-5)
-2 = 3+(-5)
-2 = -2
L = P